Share Price Impact Of Pt XL Axiata Tbk and PT Link Net Tbk Before and After The Acquisition - Masdar Ryketeng; Andi Luti Junillah; Nurul Ida Ariqah; Siti Nuraeni; Amanda Putri (Jurnal Ilmiah Akuntansi Peradaban, 2024)
The purpose of this study is to be able to analyze the impact of PT XL Axiata's stock price before and after the Link Net acquisition to help readers understand the direct impact of the acquisition on the company's stock price. The research sample is the stock price before and after the acquisition of PT XL Axiata and PT Link Net from January 1, 2021 to May 1, 2023. Data collection in this study is secondary data. There is a significant difference between PT XL Axiata and PT Link Net and stock prices can affect market sentiment. PT LINK Net shows a significant difference in share price before and after the acquisition of XL Axiata. Keyword: Impact, Acquisition, Stock Price, Company Performance